Alice adventures in wonderland - Carroll, Lewis (London : Macmillan Children's Book, 2015)
This world-famous classic with its cast of much-loved characters transformed children's literature and brought lasting fame to Charles Lutwidge Dodgson (1832-98), writing as Lewis Carroll. First published in 1865, with illustrations by Punch cartoonist Sir John Tenniel, the book remains unsurpassed in its universal appeal.